Assessment of Liver Function for Evaluation of Long-Term Outcomes of Intrahepatic Cholangiocarcinoma: A Multi-Institutional Analysis of 620 Patients - Li, Hui; Li, Jiaxin; Wang, Jinju; Liu, Hailing; Cai, Bole; Wang, Genshu; Wu, Hong (Frontiers in Oncology, 2020)
Background: Liver function is a routine laboratory test prior to curative liver resection. It remains unclear for the albumin-bilirubin (ALBI) grade and albumin-to-alkaline phosphatase ratio (AAPR) in predicting long-term outcomes of surgically treated patients with intrahepatic cholangiocarcinoma (ICC). Methods: This study investigated the correlation between ALBI grade and AAPR with overall survival (OS) after liver resection, then compared their accuracy to Child-Pugh score. The Harrell’s concordance index (C-index) and akaike information criterions (AICs) were used to compare accuracy of models. Results: A total of 620 ICC patients were included, 477 in derivation cohort and 143 for validation. 0.348 was identified as the cut-off value for AAPR after calculating Youden index. In derivation cohort, elevated ALBI grade was associated with worse prognosis [hazard ratio (HR): 1.751, 95% confidence interval (CI): 1.329 to 2.306], decreased AAPR value was correlated to shorter OS (HR: 1.969, 95%CI: 1.552 to 2.497). Multivariate analysis suggested the ALBI grade, AAPR, CA19-9, tumor number and microvascular invasion were independent prognostic predictors for OS. ALBI grade and AAPR showed more accuracy in evaluate OS for surgically treated ICC patients than Child-Pugh score (C-index: 0.559, 0.600 versus 0.528; AIC: 3023.84, 3007.73 versus 3034.66). Our findings were validated in an independent cohort from another clinical center. Conclusions: Importantly, the ALBI grade and AAPR showed greater discriminatory power than Child-Pugh score in assessing long-term outcomes following hepatectomy for ICC. The AAPR was more accurate than the ALBI grade. It was beneficial to consider the ALBI grade and AAPR as useful surrogate markers to identify patients at risk of poor postoperative outcomes.